Sporulated Toxoplasma gondii oocysts from feces of domesticated and stray cats in Manila, Philippines - Milanez, Giovanni De Jesus; Masangkay, Frederick Ramirez (Asian Journal of Biological and Life Sciences, 2020)
Toxoplasma gondiihas been an emerging public health concern due to its ability to infect a wide range of mammalian and non-mammalian host. This study aimed to gather evidence on the presence ofT. gondiioocyst from feces of stray and domesticated cats in Manila, Philippines to provide a baseline data on the potentially infective oocysts that may be transmitted to the general public living in close proximity and in direct contact with the definitive host. A total of 70 cat feces (domesticated = 35; stray cats = 35) were investigated for the presence ofT. gondiioocyst using Sheather’s sucrose floatation technique and light microscopy examination. Two sample z-tests of proportion using STATA software was used to determine if there was a significant difference between the proportion of stray and domesticated cat feces positive forT. gondiioocysts with level of significance set at 0.05 (α=0.05). A total of 6 stray cat feces were positive forT. gondiioocyst. The overall prevalence was 9% (6/70) while domesticated and stray cat prevalence were 0% (0/35) and 17.14% (6/35), respectively. The present study provides the baseline data of the prevalence ofT. gondiiinfected cats in Manila and to the best of our knowledge, the first report of the potential number of cats shedding oocyst in a metropolitan environment in the Philippines.
Keywords: Cat; oocyst; Philippines; Sporulated; Toxoplasma